Aberrant static and dynamic functional network connectivity in heart failure with preserved ejection fraction. (13th May 2022) - Jiang, Liang; Liu, Shenghua; Li, Lin; Wu, Wen; Ai, Zhongping; Chen, Huiyou; Yin, Xindao; Chen, Yu‐Chen
Abstract: Aims: Heart failure may lead to brain functional alterations related to cognitive impairment. This study aimed to detect alterations of static functional network connectivity (FNC) and dynamic FNC in heart failure with preserved ejection fraction (HFpEF) and to estimate the association between the altered FNC and clinical features related to HFpEF. Methods and results: The clinical and resting‐state functional magnetic resonance imaging (fMRI) data of HFpEF patients ( n  = 35) and healthy controls (HCs) ( n  = 35) were acquired at baseline. Resting‐state networks (RSNs) were established based on independent component analysis (ICA) and FNC analyses were performed. The associations between the FNC abnormalities and clinical features related to HFpEF were analysed. Compared with HCs, HFpEF patients showed decreased functional connectivity within the default mode network, left frontoparietal network, and right frontoparietal network and increased functional connectivity within the right frontoparietal network and visual network. Negative correlations were observed between decreased dynamic FNC and the left ventricular end‐diastolic diameter (LVDd) ( r  = −0.435, P  = 0.015) as well as the left ventricular end‐systolic diameter (LVDs) ( r  = −0.443, P  = 0.013). Conclusions: The FNC disruption and altered temporal properties of functional dynamics in HFpEF patients may reflect the neural mechanisms of brain injury after HFpEF, which may deepen our understanding of the disease.